Pembinaan SAD Muratara Dalam Perspektif Ham Dan Maslahah Mursalah - Rahma, Aneka (STAI Bumi Silampari, 2025)
The opening of large-scale oil palm plantations in Muratara Regency requires the SAD community to be eliminated from their original roaming area. This is contrary to the mandate of law Number 39 of 1999 concerning human rights. The purpose of this study is to find out the Development of the Orang Asli Tribe (SAD) in the Perspective of Human Rights and Maslahah Mursalah. The type of research used by the author is empirical legal research. Empirical legal research, in other words, is a type of sociological research and can also be called field research, which examines the applicable legal provisions and what happens in reality in society. Based on the research that has been carried out, it can be concluded that the process of relocating the Orang Dalam Tribe (SAD) of Mandi Angin Village, Muratara Regency is quite good, which is marked by the actions of the SAD community who are quite orderly in following all instructions from the relocation implementing officials. Meanwhile, the Guidance for SAD Relocated in Mandi Angin Village is in accordance with Law Number 39 of 1999 concerning Human Rights, especially Article 9 Paragraph (1-3). As for the perspective of Mashlahah, this policy can be classified as maslahah mursalah mu'tabarah, which is a form of benefit that is not explicitly stipulated in the nash but is urgently needed in the context of the times and social changes.